PENGARUH PENERBITAN SUKUK KOORPORASI SEBAGAI INSTRUMEN INVESTASI TERHADAP VARIABEL MAKRO EKONOMI DI INDONESIA PERIODE 2012-2018 - Halilladi, Tridenov Habibie; Cahyono, Hendry (Universitas Negeri Surabaya, 2020)
The presence of corporate sukuk in the national economy can be said to be developing rapidly, the existence of legality and is believed to be one of the investment instruments for economic growth. This thesis research intends to test the effect of the issuance of sukuk which is said to be an investment instrument and it’s impact on macroeconomic variables in Indonesia, especially the variable interest rates and inflation in the period 2012-2018. This testing is quantitative based on the amount of secondary data collected as much as 84 months in the 2012-2018 period. And analyzed by panel data regression common effect model techniques processed using Stata 14. Based on the results of the analysis test, it is found that the issuance of sukuk as an investment instrument has a major effect on macroeconomic variables, especially long term, however, in the short term, the bank launches liquidity so that the national economy is stable, especially banking.